Green Computing Awareness, Knowledge, and Practices among University Students in Saudi Arabia - Luisa PINTO; Allwiya ALLUI; Shafiq ALAM (Communications of International Proceedings, 2021)
Universities can nowadays be regarded as ‘small cities’ due to their large size, population, and the various complex activities taking place in campuses, which have some serious direct and indirect impacts on the environment. Increased global warming resulting from computing activities (which accounts to over 50% of activities in the universities) is not likely to stop unless the people directly involved in the activities become responsible and conscious users of energy. The main goal of this study is to understand the awareness, the level of knowledge regarding green computing, and the actual practices among university students in Saudi Arabia. To achieve the objectives of this research, a survey based on literature review, was designed to obtain evidence about the awareness, knowledge and green computing practices. Descriptive statistics, independent-samples t-tests and bivariate correlation will be employed to analyse the data.
Keywords: Green Computing; Knowledge; Practices; Students; Energy; Environment